ESTETIKA PROFETIK DALAM NOVEL LAYALI TURKISTAN KARYA NAJIB AL-KAILANI - Mu'id, Iqbalul; Milal, Mukhamad Syaiful; Rahayu, Mundi (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2023)
The policies of the Chinese and Russian colonizers on cross-marriage between Turkistan women and Chinese soldiers and merchants created separate social problems for the Turkistan people. Therefore, this study uses the tools of sociology of literature to dismantle prophetic aesthetics in the novel Layali Turkistan. This study tries to describe the prophetic aesthetics in the novel Layali Turkistan by Najib Kailani with the tools of literary sociology. The main focus of this research is to dismantle the process of dehumanization that occurred to the Turkistani people as a result of the Chinese and Russian communist invaders. The process of dehumanization creates a prophetic aesthetic in the form of humanization, liberation, and transcendence for the Turkmen people. This study used the descriptive-qualitative method. This method is used because the source of research data is in the form of textual data consisting of dialogs and statements in material objects. The results of this study show that, first, the humanization value is embodied by the character Naghmatullail by marrying the Chinese commander according to Islamic law, so that Naghmah easily instills humanistic values. Second, King Komul's decision to oppose and combat Chinese communist policies is a form of aesthetic liberation for the people of Turkistan. Third, when King Komul explains the essence of heaven, the divine consciousness is deeply embedded in the person of the Turkistan people.